Home ranges of introduced rats on Christmas Island: A pilot study. (21st December 2012) - Low, Bing W.; Mills, Harriet; Algar, David; Hamilton, Neil
Summary Understanding the spatial ecology of invasive rats (Rattus spp.) is necessary to inform management actions to reduce their impact on native flora and fauna. This study investigates home range sizes of exotic rats around seabird colonies and urban areas on Christmas Island, where rat predation is suspected to be adversely affecting fledgling success among local seabirds. It was hypothesised that rat home range sizes would be smaller in urban areas owing to more consistent food availability. Home ranges of male rats were significantly larger compared with their female counterparts, with male rats maintaining larger home ranges in urban areas compared with seabird colonies. Conversely, female rats had smaller home ranges in urban areas compared with seabird colonies. Our findings suggest a possible correlation between the spatial distribution of food resources and home range size. Additionally, the spatial distribution of breeding females across the landscape had a significant influence on the home ranges of male rats. These findings have important implications for proposed efforts to manage rat populations on Christmas Island, while also providing valuable information regarding the ecology of invasive rats on tropical islands.